COVID-19 Diaries: A Peek into the Experiences of Students Studying Language and Literature Courses During the Pandemic - Tolentino, Oliveth; Manlapig, Belle; Flores, Kathleen; Naidas, Michael; Agum, Arjem Noryn; Parinas, Sabina (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Schooling during the COVID-19 pandemic has had disparate effects on the academic world. Qualitative studies on the experiences of students studying language and literature during the pandemic are limited. Therefore, this narrative research aimed to explore the experiences of college students in a faith-based institution in the Philippines while studying language and literature during the pandemic. A total of 15 student narratives about language and literature classes in the academic year 2020-2021 were purposively selected. Content analysis was done to analyze the narratives. The results revealed that most of the challenges stemmed from the mental, physical, and social inconveniences experienced by the students when attending their classes. The specific problems were related to the high stress stemming from the academic changes in the learning format and the academic requirements students find difficult to cope with. It is concluded that although these academic challenges are apparent among students studying language and literature, there are ways to address them. Based on the results, it is recommended to do more specific research on the unprecedented mental health concerns of the students during the pandemic, with a more specific plan on student support programs to ease the mental, physical, and social burdens of the students. Keywords : mental challenges, physical challenges, social challenges, pandemic